Functional analysis of ZmCOP1 and ZmHY5 reveals conserved light signaling mechanism in maize and Arabidopsis. Issue 3 (5th April 2020) - Huai, Junling; Jing, Yanjun; Lin, Rongcheng
Abstract : Plants have evolved light signaling mechanisms to optimally adapt developmental patterns to the ambient light environments. CONSTITUTIVE PHOTOMORPHOGENIC1 (COP1) and LONG HYPOCOTYL5 (HY5) are two critical components in the light signaling pathway in Arabidopsis thaliana . COP1 acts as an E3 ubiquitin ligase that targets positive regulators, such as HY5, leading to their degradation in darkness. However, functional analysis of the COP1‐HY5 module in maize ( Zea mays ) has not been reported. Here, we investigated the expression patterns and roles of the COP1 and HY5 orthologs, ZmCOP1 and ZmHY5, in regulating photomorphogenesis. These two genes have high amino acid identities with their Arabidopsis homolog and were both regulated by light. Subcellular localization assay showed that ZmCOP1 was distributed in the cytosol and ZmHY5 localized in the nucleus. Exogenous expression of ZmCOP1 rescued the physiological defects of the cop1‐4 mutant, and expression of ZmHY5 complemented the long hypocotyl phenotype of the hy5‐215 mutant in Arabidopsis. Yeast two‐hybrid and fluorescence resonance energy transfer assays showed that ZmCOP1 interacted with ZmHY5. Our study gains insight into the conserved function and regulatory mechanism of the COP1‐HY5 signaling pathway in maize and Arabidopsis.